Effect of light-curing silver diamine fluoride on microtensile bond strength of primary carious dentin restored with glass ionomer cement: In vitro study - Haradwala F Zaineb; J. Jasmin Winnier; Soni M Arwa (Wolters Kluwer Medknow Publications, 2023)
Introduction: Silver diamine fluoride (SDF) has been used as a caries arresting agent. The application protocol of SDF is unclear. Some clinicians prefer to light cure SDF to accelerate the hardening of SDF; however, the effect of the same on bond strength of the restoration is unknown. This study aimed to determine the effect of light-curing SDF on microtensile bond strength (µTBS) of primary teeth restored with glass ionomer cement (GIC). Materials and Methods: Seventeen carious primary molars were sectioned through the middle of the carious lesion and allocated randomly to three groups. Group 1-SDF application followed by GIC restoration, group 2-SDF application followed by light cure of SDF and restored with GIC, group 3-control: GIC restoration without SDF application (n = 11). The samples were stored in artificial saliva; evaluated for µTBS under universal testing machine until failure. The failure mode was evaluated using stereomicroscope at 40× magnification. Results: µTBS of the groups were compared using Kruskal-Wallis test, which showed a statistically significant difference between the groups (P < 0.05). Dunn's post hoc test revealed a significantly higher bond strength with group 2 (4.15 ± 2.51) compared to group 1 (1.40 ± 0.49) (P value 0.022). The failure modes for each group were carried out with chi-square test which revealed no statistically significant difference. Conclusion: Light-curing SDF prior to application of GIC resulted in significantly greater bond strength when compared to non-light-cured SDF.